PROCEDURE FOR ORGANIZATION, TYPES AND ACTIVITIES OF ARBITRATION COURTS (World Bulletin of Education and Learning, 2025)
This article covers concepts such as "Issues of cooperation between arbitration courts and state courts «, "Interrelationship between arbitration courts and state courts", "The role of arbitration courts and its importance today", "Prospects for the use of arbitration in problematic situations facing state courts".
Keywords: Arbitration courts, state courts, alternative dispute resolution, judicial reform, arbitration agreement, judicial cooperation, legal framework of arbitration, Uzbekistan judicial system.